2017
DOI: 10.1590/01047760201723042292
|View full text |Cite
|
Sign up to set email alerts
|

Different Stability Methods for Cultivar Recommendation in Elephant-Grass for Energy Purposes in Brazil

Abstract: The elephant-grass undergoes successive cutting and periodical evaluations that it possible to identify clones with high stability for dry matter production, which can be used for energy production. The present study was carried out to evaluate stability dry matter yield for different parametric and non-parametric methods in elephant grass genotypes for biomass production undergoes successive cutting in the agroclimatic conditions of the Norte Fluminense (RJ, Brazil). The variable measured in the 40 genotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…These findings were consistent with the observed negative correlation between fiber components and CP, IVOMD, and ME. A previous report [46] also indicated that an increase in fiber components reduces cellular nutrients, such as crude protein and digestibility. Furthermore, a PCA partitioned the genotypes into three cluster groups; for example, genotypes in cluster one showed high CP, IVOMD, and ME values, while genotypes in cluster two showed high fiber components and forage biomass yield in both wet and dry seasons.…”
Section: Genotypic Performance For Feed Nutritional Qualitymentioning
confidence: 85%
“…These findings were consistent with the observed negative correlation between fiber components and CP, IVOMD, and ME. A previous report [46] also indicated that an increase in fiber components reduces cellular nutrients, such as crude protein and digestibility. Furthermore, a PCA partitioned the genotypes into three cluster groups; for example, genotypes in cluster one showed high CP, IVOMD, and ME values, while genotypes in cluster two showed high fiber components and forage biomass yield in both wet and dry seasons.…”
Section: Genotypic Performance For Feed Nutritional Qualitymentioning
confidence: 85%
“…The significance of the G × H interaction demonstrates that the relative performance of the genotypes was not consistent throughout the successive harvests. Significant G × H interactions in the evaluation of elephant grass for energy generation over several harvests were also reported by Rocha et al (2015), Araújo et al (2017), and Silva et al (2018b).…”
Section: Resultsmentioning
confidence: 72%
“…Therefore, investigating the interaction through methodologies of adaptability and stability shall contribute to a more in-depth analysis of the genotypes' performance. Silva et al (2018b) evaluated elephant grass at annual harvests, and joint analysis of variance showed significant effects of the genotype × harvest interaction on dry matter yield, indicating that the genotypes showed different production performances at each harvest.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation